2007
DOI: 10.1182/blood-2006-09-046748
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A potentiates CpG-mediated memory B-cell proliferation and differentiation: involvement of early activation of p38MAPK

Abstract: Foreign CpG-DNA from viruses and bacteria can activate memory B cells through binding to toll-like receptor 9, and this pathway has been hypothesized to be involved in the continuous activation of memory B cells ensuring life-long humoral immunity. In this study, we demonstrate that retinoic acid (RA) is a potent coactivator of this pathway in human B cells. RA enhanced the CpG-mediated proliferation of CD27 ؉ memory B cells, and the proliferative response was accompanied by increased immunoglobulin (Ig) secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 71 publications
3
51
1
Order By: Relevance
“…All-trans retinoic acid (RA) is the main vitamin A metabolite involved in immune regulation (6), where its primary function is to regulate gene transcription via binding to the nuclear receptors retinoic acid receptors (RARs) and retinoic X receptors (7). Although it is well established that vitamin A is crucial for an optimal immune defense, its effects on different cells of the immune system vary, depending on the type of costimulation involved (8,9). Our group demonstrated previously that, although RA inhibits B cells stimulated via the BCR (9)(10)(11), it can enhance immunologic responses in B cells when the cells are stimulated through TLR9 alone (9) or in combination with the TLR RP105 (12).…”
Section: Ommon Variable Immunodeficiency (Cvid) Is the Most Commonlmentioning
confidence: 99%
“…All-trans retinoic acid (RA) is the main vitamin A metabolite involved in immune regulation (6), where its primary function is to regulate gene transcription via binding to the nuclear receptors retinoic acid receptors (RARs) and retinoic X receptors (7). Although it is well established that vitamin A is crucial for an optimal immune defense, its effects on different cells of the immune system vary, depending on the type of costimulation involved (8,9). Our group demonstrated previously that, although RA inhibits B cells stimulated via the BCR (9)(10)(11), it can enhance immunologic responses in B cells when the cells are stimulated through TLR9 alone (9) or in combination with the TLR RP105 (12).…”
Section: Ommon Variable Immunodeficiency (Cvid) Is the Most Commonlmentioning
confidence: 99%
“…17,18 We have previously shown that RA enhances proliferation and Ig-production in B cells stimulated via TLRs. 23,24,31 In the present study we provide a novel mechanism whereby vitamin A may stimulate the immune system, by demonstrating that RA-induced secretion of IgG from TLR9-and CD180-stimulated human B cells involves ULK1-mediated autophagy. Hence, RA promoted both the formation of LC3B-II and the expression of ULK1, whereas blocking autophagy by knockdown of ULK1 reduced the RA-mediated production of IgG.…”
Section: Discussionmentioning
confidence: 76%
“…8,9 Having previously demonstrated the stimulatory effect of RA on IgG-production in normal human B cells activated via TLR9 alone or in combination with CD180, 23,24,31 we here investigated the possible involvement of autophagy in this process. The MAP1LC3/LC3 (microtubuleassociated protein 1 light chain 3) protein is a widely used and accepted marker of phagophores and autophagosomes, 32 and is commonly used to monitor the levels of autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations